Jasper's beanstalk - Butterworth, Nick ([s.l.] : Aladdin Paperbacks, 1993)
Japer hopes to grow a beanstalk, but becomes discouraged when the bean he plants doesn't grow after a week.
Keywords: Beans-Fiction; Cats-Fiction